2012
DOI: 10.1186/1471-2393-12-134
|View full text |Cite
|
Sign up to set email alerts
|

Improved quality of management of eclampsia patients through criteria based audit at Muhimbili National Hospital, Dar es Salaam, Tanzania. Bridging the quality gap

Abstract: BackgroundCriteria-based audits (CBA) have been used to improve clinical management in developed countries, but have only recently been introduced in the developing world. This study discusses the use of a CBA to improve quality of care among eclampsia patients admitted at a University teaching hospital in Dar es Salaam Tanzania.ObjectiveThe prevalence of eclampsia in MNH is high (≈6%) with the majority of cases arriving after start of convulsions. In 2004–2005 the case-fatality rate in eclampsia was 5.1% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 14 publications
(19 reference statements)
2
26
0
1
Order By: Relevance
“…A similar inverse relationship between AMTSL practice and PPH incidence was also observed after the quality improvement interventions in Niger and Mali [25]. Similar results were also observed in studies of hospitals in Tanzania [23] following quality improvement interventions [26]. …”
Section: Discussionsupporting
confidence: 78%
“…A similar inverse relationship between AMTSL practice and PPH incidence was also observed after the quality improvement interventions in Niger and Mali [25]. Similar results were also observed in studies of hospitals in Tanzania [23] following quality improvement interventions [26]. …”
Section: Discussionsupporting
confidence: 78%
“…The principally agreed-upon criterion for diagnosis is a prolonged active labour, implying a failure of labour to progress due to cephalopelvic disproportion [15] that requires surgical or assisted vaginal delivery [5]. Maaloe et al [12] and Kidanto et al [37] reported on failure to interpret signs of prolonged labour as obstructed labour in both rural and urban health facilities. Unlike the Malawi audit [9], the agreed-upon diagnosis in our study included additional minor criteria that improved the standards of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…As others have confirmed, a mandatory patient review by a senior obstetrician and a more efficient timeline for intervention, either singly or in combination resulted in improved care [37,39,40]. However, awareness of care providers that an evaluation was being conducted might also have positively or negatively influenced the changes in practice that were recorded [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These CBAs have shown positive improvement in the quality of care in some low income counties [7]. This study had an aim of assessing the quality of care given to inpatients with PPH and severe pre-eclampsia in St. Francis Hospital Nsambya as a way of reducing maternal mortality.…”
Section: Introductionmentioning
confidence: 99%